Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-04T21:21:44+01:00
A)4x-3y-10x-4y+7y=-6x
b)(7-x)+(2+2x-3xy)-(4xy-5x)=9-4x+6xy
c)(5m-8)+(4-7m)-(m-5)-(20+4m)=5m+11
d)-2(3a+5b)+3(4b-6a)=6a+10b+12b-18a=-12a+22b
1 5 1
2010-02-04T21:26:54+01:00
A)4x-3y-10x-4y+7y= -6x

b)(7-x)+(2+2x-3xy)-(4xy-5x)= 9-4x+6xy

c)(5m-8)+(4-7m)-(m-5)-(20+4m)= 5m+11

d)-2(3a+5b)+3(4b-6a)=6a+10b+12b-18a= -12a+22b
2010-02-04T23:29:55+01:00
A)
4x-3y-10x-4y+7y= -6x
b)
(7-x)+(2+2x-3xy)-(4xy-5x)= 7-x+2+2x-3xy-4xy+5x = 9+6x-7xy
c)
(5m-8)+(4-7m)-(m-5)-(20+4m)= 5m-8+4-7m-m+5-20-4m = -7m-19
d)
-2(3a+5b)+3(4b-6a)= -6a-10b+12b-18a = -24a+2b